Qualitative Methods in Pharmacy Research - Gisselle Gallego; Lotte Stig Nørgaard (MDPI AG, 2018)
Over the past years, there has been an increase in the use of qualitative methods in health services research, including pharmacy research. Pharmacy practice researchers can use these methods to understand, explain, discover, and explore both patients’ and health care practitioners’ thoughts, perceptions, and feelings. Qualitative research can also be used for the “democratisation” of research methods through research that is inclusive, collaborative, and involves partnerships and co-production. There is a wide spectrum of qualitative research methods that might be used in pharmacy research. This Special Issue showcases five articles in different settings and countries with diverse participants that seek to develop, explore, describe, and identify. These articles provide further insights into important pharmacy questions with the ultimate goal of helping improve health and well-being.